Consumer Legal Protection Against Misleading Advertisements In Electronic Transactions Of Beauty Products (A Comparative Study Between Indonesia And South Korea) - Tsabitah Rahmah Adfari; Citraresmi Widoretno Putri (Jurnal Daulat Hukum, 2026)
This study aims to analyze legal regulations and compare consumer protection mechanisms against misleading advertising in electronic transactions of beauty products in Indonesia and South Korea. The method used is normative juridical research with a comparative legal approach, through a literature review of primary, secondary, and tertiary legal materials, which are then analyzed qualitatively. The results of the study indicate that both countries have a relatively comprehensive legal framework for regulating misleading advertising, but with different characteristics. Indonesia relies on scattered regulations such as the Consumer Protection Law, the Electronic Information and Transactions Law, and supervision by the Food and Drug Supervisory Agency. Meanwhile, South Korea implements a more integrated and proactive system through the Cosmetics Act, the Act on Fair Labeling and Advertising, and the Ministry of Food and Drug Safety, supported by regulations responsive to technological developments such as the regulation of dark patterns, collective dispute resolution mechanisms, and stricter sanctions including reverse burden of proof and potential punitive damages. These findings indicate that although Indonesia has an adequate legal basis, institutional strengthening, regulatory harmonization, and technological adaptation are needed to improve the effectiveness of consumer protection in the digital era.